(untitled) (World of finance, 2019)
Introduction. One of the most important and most urgent task of improving budget management in Ukraine is timely identification of budgetary risks and ensure its effective management. The management of budget risks, including budget funding risks requires first of all, studying factors of their occurrence and identifying ways to minimize them. Purpose. The purpose of the article is to distinguish risk factors of budget funding and determining ways to minimize them. Results. Based on the author’s definition of “budget funding risks” factors of budget funding risks in terms of its participants are singled. The factors of budget funding risks associated with the performance of its functions by the main managers of budget funds, by the Ministry of Finance of Ukraine, by the State Treasury Service of Ukraine and by the State Audit Service of Ukraine are analyzed. The main ways of minimizing risks are offered. Conclusion. The factors of budget funding risks that were singled create the probability of adverse situations and negative results. In our opinion, the main way to minimize budget funding risks is compliance by all participants of the provisions of existing legal acts that govern the order of execution of expenditure part of the budget. Also we offer to develop and approve the Order regarding the “Budget funding risks: definition, classification, factors and ways of minimizing” at the Ministry of Finance of Ukraine.